Hubungan Kecerdasan Emosional dengan Minat Belajar Siswa Kelas XI MIPA di SMA Negeri 15 Bone - Astutika; Nurmi; Romi Adiansyah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to prove the relationship between Emotional Intelligence and Learning Interest of XI MIPA Class Students at SMA Negeri 15 Bone. This research is quantitative research with correlational methods. The data processed are data on the population and student samples, questionnaires, interviews and documentation, using a sampling technique, namely purposive sampling with a sample of XI MIPA 2 class of 30 students. The data collection method in this study used a Likert scale. The data analysis technique used is Product Moment Correlation. The results of this study show the product moment correlation coefficient value rxy = 305 with a significance of p = 0.000 p < 0.05, meaning that there is a positive relationship between emotional intelligence and interest in learning in students at SMA Negeri 15 Bone, with a determinant coefficient of (r2) 0.29 or 96.7%, in other words the hypothesis proposed in this study is accepted.